2013
DOI: 10.1159/000347212
|View full text |Cite
|
Sign up to set email alerts
|

NOX2 Protects against Prolonged Inflammation, Lung Injury, and Mortality following Systemic Insults

Abstract: The systemic inflammatory response syndrome (SIRS) is a clinical condition occurring in intensive care unit patients as a consequence of both infectious and noninfectious insults. The mechanisms underlying resolution of SIRS are not well characterized. NOX2 (NADPH oxidase 2)-derived reactive oxygen species are critical for killing of certain pathogens by polymorphonuclear leukocytes (PMN). Patients with chronic granulomatous disease who lack functional NOX2 are not only prone to serious infections, they also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 37 publications
6
33
0
Order By: Relevance
“…This is in agreement with the previous findings that NOX2 deficiency in mice leads to increased levels of IL-1β in the early onset of arthritis and therefore to a more severe inflammatory phenotype [35]. Moreover, NOX2-derived ROS is essential for the phagosome function and it has been considered as a barrier of sustained inflammation [56][57][58]. Hence, we hypothesize that this protective role of NOX2-generated ROS in inflammation and IL-1β production could be regulated by biglycan.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the previous findings that NOX2 deficiency in mice leads to increased levels of IL-1β in the early onset of arthritis and therefore to a more severe inflammatory phenotype [35]. Moreover, NOX2-derived ROS is essential for the phagosome function and it has been considered as a barrier of sustained inflammation [56][57][58]. Hence, we hypothesize that this protective role of NOX2-generated ROS in inflammation and IL-1β production could be regulated by biglycan.…”
Section: Discussionsupporting
confidence: 93%
“…Because an absence of Nox2 has been found to upregulate proinflammatory responses (eg, production of IL-1β, IL-6 , and TNF-Îą), thereby aggravating arthritis 18 and systemic inflammatory response syndrome, 19 as well as chronic granulomatous disease, 15 Nox2 may possess anti-inflammatory-like effects even in inflammatory vascular diseases. Consistent with previous findings, 20 we found that NOX2 contributes to reactive oxygen species generation in macrophages, although we also found that a Nox2 deficiency in macrophages potentiated the secretion of IL-1β and MMP9.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory became interested in neutrophil responses to TLR2 agonists after finding complex and unexpected interactions between TLR2 ligation and the NADPH oxidase 2 using a murine model of systemic inflammation elicited by injection of a TLR2 agonist (15, 16). In the current study, we sought to further define human PMN priming responses to TLR2 ligands in vitro/ex vivo .…”
Section: Introductionmentioning
confidence: 99%